Religiositas TNI : refleksi pemikiran dan kepribadian Jenderal Besar Soedirman - Nasution, Asren, 1965-; Sutrisno, try; Soedirman, Mohd. Teguh; Djasit, Saleh; Harahap, Syahrin (Rawamangun, Jakarta, Indonesia : Kencana, 2003)
Contribution of General Sudirman, 1st Commander-in-Chief of the Indonesian Armed Forces before the independence, in religious aspects for the Armed Forces members
Originally presented as the author's thesis (master's--IAIN Sumatera Utara, 2001) under title: Pemikiran keagamaan Jenderal Besar Soedirman
Bibliography: p. [201]-205
Keywords: Sudirman, -- 1915?-1950; Indonesia. -- Angkatan Darat -- Biography; Generals -- Indonesia -- Biography